2022
DOI: 10.1364/ao.471280
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Fano-resonance-based temperature sensor by side-coupling double cavities to waveguide in photonic crystals

Abstract: Optical sensors are widely used for temperature measurement in chemistry, biomedical detection, and food processing industries. In this paper, we present a highly sensitive temperature sensor based on the Fano resonance in two-dimensional photonic crystals. A carefully designed double cavity is used within the photonic crystals to symmetrically side-couple to a line-defect waveguide. Due to the direct and indirect coupling between two cavities, we found an asymmetric Fano-like line shape in the transmission sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This resonant behavior offers potential applications in various fields, including sensing, optical filtering, and nonlinear optics. Previous studies have indicated that the geometric parameters of the unit structure influence the Fano resonance [4][5][6][7]. Thus, the optimum design of these unit structures plays a crucial role in both generating and modulating the Fano resonance.…”
Section: Introductionmentioning
confidence: 99%
“…This resonant behavior offers potential applications in various fields, including sensing, optical filtering, and nonlinear optics. Previous studies have indicated that the geometric parameters of the unit structure influence the Fano resonance [4][5][6][7]. Thus, the optimum design of these unit structures plays a crucial role in both generating and modulating the Fano resonance.…”
Section: Introductionmentioning
confidence: 99%